2016
DOI: 10.1128/iai.00148-16
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Prominent Roles for Enzymes of Plasmodium berghei Heme Biosynthesis in Sporozoite and Liver Stage Maturation

Abstract: Malarial parasites have evolved complex regulation of heme supply and disposal to adjust to heme-rich and -deprived host environments. In addition to its own pathway for heme biosynthesis, Plasmodium likely harbors mechanisms for heme scavenging from host erythrocytes. Elaborate compartmentalization of de novo heme synthesis into three subcellular locations, including the vestigial plastid organelle, indicates critical roles in life cycle progression. In this study, we systematically profile the essentiality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 49 publications
(71 reference statements)
8
34
0
Order By: Relevance
“…This confirms previous findings [12, 15] that the parasite heme synthesis enzymes do not play an essential role in the early mosquito life stages in P . berghei .…”
Section: Resultssupporting
confidence: 92%
“…This confirms previous findings [12, 15] that the parasite heme synthesis enzymes do not play an essential role in the early mosquito life stages in P . berghei .…”
Section: Resultssupporting
confidence: 92%
“…For example, we found that LYTB is upregulated at 2 and 4 hpi, indicating isoprenoids may be important at this time. Although the FASII and de novo heme biosynthesis pathways have been genetically and chemically validated as essential to the late liver stages, less is known about isoprenoid biosynthesis during the early liver stages (34,35). When intracellular sporozoites metamorphosize to replication-competent trophozoites, most organelles are expelled at the exclusion of the nucleus, mitochondrion, and apicoplast (10).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas protein-driven hemozoin formation has been postulated before (101), lipid-driven mechanisms (102,103) and an autocatalytic process have also been proposed (104). Unsurprisingly, heme synthesis is not essential for Plasmodium during the intraerythrocytic development, but the pathway becomes fitness-conferring during liver stages and is essential for development in the mosquito (105)(106)(107)(108)(109). Specifically, the loss of FC impairs male gamete formation and ablates oocyst formation in mosquitoes, indicating that Plasmodium can utilize salvaged heme but relies on its synthesis when levels of exogeneous heme become limiting within the insect vector (105,106).…”
Section: Hemementioning
confidence: 99%